Physico‐mechanical evaluation of the aptitude of berries of red wine grape varieties to resist the compression in carbonic maceration vinification. (3rd December 2012) - Giacosa, Simone; Torchio, Fabrizio; Segade, Susana Río; Gaiotti, Federica; Tomasi, Diego; Lovat, Lorenzo; Vincenzi, Simone; Rolle, Luca
Summary By texture analysis tests, the ability of berries to resist rupture under compression load during intracellular fermentation was studied for twenty‐three red wine grape varieties. The softest berries were associated with Ancellotta (1.72 N), Dolcetto (1.79 N), Gamay (2.26 N) and Schiava gentile (2.29 N) cultivars. The hardest berries corresponded to Franconia and Bonarda cultivars (4.02–4.03 N). High resistance to splitting was also detected for Grenache, Raboso, Marzemino, Negramaro, Montepulciano and Croatina cultivars (3.50–3.95 N). The differentiating power of the mechanical variables of the whole berry and skin was assessed by univariate and multivariate analysis. Relationships among the instrumental berry hardness and other physical and mechanical properties were also investigated. The results obtained suggest that the manufacture of carbonic macerated wines should be planned considering the berry hardness, and it represents a new variable that should be considered in selecting the most appropriate wine grape variety to elaborate these wines.